2007
DOI: 10.1016/j.bbrc.2007.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of insulin secretion and GLUT4 trafficking by the calcium sensor synaptotagmin VII

Abstract: Insulin regulates blood glucose by promoting uptake by fat and muscle, and inhibiting production by liver. Insulin-stimulated glucose uptake is mediated by GLUT4, which translocates from an intracellular compartment to the plasma membrane. GLUT4 traffic and insulin secretion both rely on calcium-dependent, regulated exocytosis. Deletion of the voltage-gated potassium channel Kv1.3 results in constitutive expression of GLUT4 at the plasma membrane. Inhibition of channel activity stimulated GLUT4 translocation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
44
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…Elimination of synaptotagmin-7 alone impairs Ca 2ϩ -triggered exocytosis, with an Ϸ50% decrease observed by capacitance measurements or amperometry in good agreement with recent data from insulin-secreting cells (31,32). 2.…”
Section: Discussionsupporting
confidence: 74%
“…Elimination of synaptotagmin-7 alone impairs Ca 2ϩ -triggered exocytosis, with an Ϸ50% decrease observed by capacitance measurements or amperometry in good agreement with recent data from insulin-secreting cells (31,32). 2.…”
Section: Discussionsupporting
confidence: 74%
“…In chromaffin cells, KO of Syt1 alone abolishes the fast phase of exocytosis (7,8), whereas double KO of Syt1 and Syt7 abolishes all major phases of exocytosis, which together account for more than 90% of Ca 2+ -triggered fusion (9). Similar results were obtained for Syt1, Syt7, and Syt9 in other neuroendocrine cells (13)(14)(15)(16)(17)(18).…”
supporting
confidence: 69%
“…It has previously been shown that Kv1.3 is involved in weight maintenance, diet-induced obesity, peripheral glucose uptake and insulin sensitivity [18][19][20][21] We now demonstrate that gene-targeted deletion of Kv1.3 in MC4R-null mice, a genetic model of obesity, reduces adiposity and fasting leptin levels, without changing overall growth, fasting bloodglucose and serum-insulin. Basal or light-phase metabolically active mass-specific metabolic rate and locomotor activity were not affected by genetic deletion of Kv1.3 in MC4R-null mice but dark-phase locomotor activity and been shown by our group to have no difference in metabolism in animals completely acclimated to the metabolic chambers.…”
Section: Discussionmentioning
confidence: 51%
“…19 Acute blockade of Kv1.3 current by margatoxin or genetic deletion of Kv1.3 protein increases peripheral insulin sensitivity by increasing translocation of the glucose transporter 4 (GLUT4) to the membrane in skeletal muscle and white adipose tissue (WAT) in a Ca 2 þ dependent manner by the calcium-sensitive synaptotagmin VII. [19][20][21] We now hypothesize that loss of Kv1.3 can abrogate weight gain in a genetic model of obesity that is controlled by the central nervous system (CNS). The melanocortin-4 receptor (MC4R) is a part of the hypothalamic, anorexogenic pathway controlling metabolism and satiety, 22 and brainstem-mediated control of meal size and food preference.…”
Section: Introductionmentioning
confidence: 99%